EFL learners in the digital age: An investigation into personal and educational digital engagement - Kızıl, Aysel Şahin (My University, 2017)
To gauge the success of integrating technology into classrooms which is among the popular topics in the field of language learning, there is a need to understand how end users, language learners, use technology and bear the characteristics of digital learner as claimed for the current generation of learners. To this end, this study collected data through a survey design from 1163 university level English as a Foreign Language (EFL) learners to provide cross-cultural, empirical evidence towards building an accurate picture of EFL learners in the digital age. Data were analysed through factor analysis to identify meaningful patterns of technology use, descriptive statistics and correlations to explore the relationships between technology use patterns, language achievement and digital characteristics. Findings suggest that EFL learners are digital learners at a moderate level and the range of technology tools used both for daily and language learning purposes is not as broad as claimed for their generation. The results of the study carry implications for EFL practitioners aiming at better understanding current EFL learners and providing them with technology-integrated language instruction properly.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: EFL learners; ICT; Digital engagement; Digital learners; Digital natives